ANALISIS PELAKSANAAN PENYIMPANAN DAN PENGAMBILAN DOKUMEN REKAM MEDIS BAGIAN FILING DI RS USU - CHANDRA, ISKANDAR (LP2MTBM MAKARIOZ, 2021)
This research aims to determine the implementation of storing and returning medical record documents at Usu Hospital. This research is a descriptive research/qualitative approach. Determination of informants was carried out using purposive sampling. The informants in this study were the head of medical records and the medical records officer. Data collection by observation, interviews and documentation. The results of the research show that the management of medical record data at the North Sumatra Hospital in Medan is: First, making medical records, namely filling out forms for new patients, while old patients only show their treatment cards to be searched for medical record status by the filling officer manually. Second, Medical Record Storage (Filling), namely receiving files that are complete and arranged using a centralized system and using a direct numbering system for the time required to retrieve medical record files, namely 10-20 minutes. Third, destruction of medical records, which is carried out if the patient has not come for five years, is destroyed by shredding inactive files and then burning them. Fourth, maintaining the confidentiality of medical records, namely the custody of medical record files only allows medical record officers with legal interests. So the management of outpatient medical record data at USU Hospital has been carried out in accordance with Minister of Health Regulation Number 269/MENKES/KES/III/2008.